ANALISIS KINERJA UNIT PELAYANAN TEKNIS (UPT) TERMINAL AKAP KOTA DUMAI - Imam Habib Nurmana; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Terminal AKAP Dumai inaugurated in 2004 With Classification Type A motor vehicle can serve a common function types of service Inter City Inter Province (AKAP) / or transport across State borders, transport Inter-City In Province (AKDP) urban transport / or transport pedesaan. Terminal is managed by the Technical Implementation Unit (UPT) terminal specially formed by the Department of Transportation in the operation of the terminal and the terminal fee collection. However, the implementation of the UPT less than the maximum that causes Terminal function was not optimal. Therefore, the performance of this AKAP Terminal Unit needs to be assessed.The purpose of this study is to analyze the performance of UPT terminal AKAP, which by doing research on the performance of UPT terminal AKAP is expected to improve the quality of future performance.This type of research is descriptive qualitative. Methods of data collection using interviews, observation and documentationBased of the research result, it was known that the performance of UPT terminal AKAP Dumai in terminal management has not been implemented properly. The concept of theory used is the theory of performance according to Ratminto and Atik. Indicators in this study, such as: Tangibles, Responiveness, Responsibility, Accountability and Transparency. There is a deficiency in the indicators of responsibility. Factors affecting the performance of Terminal AKAP Dumai City are Economic, Leadership and Human Resources Factors.Keywords: Tangibles, Responsiveness, Responsibility, accountability, Transparansi